2008
DOI: 10.1111/j.1533-8525.2008.00130.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross-National Moral Beliefs: The Influence of National Religious Context

Abstract: International surveys have documented wide variation in religious beliefs and practices across nations, but does this variation in the national religious context make a difference? Building on existing theory we explain why religion should have both micro and macro-level effects on morality not sanctioned by the state and why the effects of religion differ from other forms of culture. Using two international surveys and Hierarchical Linear Modeling Techniques (HLM) we sort out the effects of national context a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
146
3
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(165 citation statements)
references
References 48 publications
3
146
3
2
Order By: Relevance
“…Rather than offering compensation to Catholics by causing spillover of social support and social influence to people outside religious communities, Protestant social contexts allow for even larger health advantages for Protestants. Building on Stark (1996), and consistent with findings from research on other outcomes such as delinquency and moral attitudes (Finke and Adamczyk 2008;Regnerus 2003;Scheepers et al 2002), this is probably due to the fact that individual religious involvement more strongly influences people's norms and conduct in a social context in which such norms and conduct are endorsed by the majority. Importantly, our results revealed that the strength of the association between religious attendance and self-assessed health varies across European countries.…”
Section: Conclusion and Discussionsupporting
confidence: 75%
“…Rather than offering compensation to Catholics by causing spillover of social support and social influence to people outside religious communities, Protestant social contexts allow for even larger health advantages for Protestants. Building on Stark (1996), and consistent with findings from research on other outcomes such as delinquency and moral attitudes (Finke and Adamczyk 2008;Regnerus 2003;Scheepers et al 2002), this is probably due to the fact that individual religious involvement more strongly influences people's norms and conduct in a social context in which such norms and conduct are endorsed by the majority. Importantly, our results revealed that the strength of the association between religious attendance and self-assessed health varies across European countries.…”
Section: Conclusion and Discussionsupporting
confidence: 75%
“…Second, given that attitudes about premarital sex may be partially shaped by laws regulating premarital sex, it would be ideal to include a measure of premarital sex regulation in the models. However, the present study lacks this measure in the analyses because I was not able to find a proper measure on government regulation regarding premarital sex; sexual behaviors are rarely covered under legal codes (Finke and Adamczyk 2008). Third, the current study examines factors that influence attitudes about premarital sex, not actual behaviors.…”
Section: Conclusion and Discussionmentioning
confidence: 94%
“…Given the higher levels of religiosity among migrants in Europe compared to natives, religion is often mentioned as a possible explanation of homophobia . Both individual and contextual religiosity affect moral beliefs about sexuality (Finke and Adamczyk 2008). However, as with disapproval of homosexuality, religiosity itself is influenced by socialization cohorts (Kelley and De Graaf 1997) and, for migrants, with origin and destination country effects (Van der Bracht, Van de Putte and Van de Velde 2014;Van Tubergen 2006).…”
Section: Northern and Western European Countries Often Reporting Verymentioning
confidence: 99%